EDUCATION FOR INTEGRAL PEACE – MEMORY, INTERCULTURALITY AND DECOLONIALITY - Jose Javier Capera Figueroa (Society Register)
Review of the book written by Eduardo Andrés Sandoval Forero (2016). Education for Integral Peace – Memory, Interculturality and Decoloniality. Bogota: ARFO Editores e Impresores LTDA. 327 pp.